OWE-23 Versatile role of secreted frizzled related protein 2 (SFRP2) in colon cancer: Potential stromal target. (June 2019) - Tabuso, Maria; Adya, Raghu; Gopalakrishnan, Kishore; James, Sean; White, Andrew; Fisk, Adrian; Dimitri, Federica; Butler, Jennifer; Christian, Mark; Arasaradnam, Ramesh P
Abstract : Introduction: Dysfunctional adipose tissue has emerged as a key contributor to colorectal cancer. However, the role of peritumoral adipose tissue (pAT) in colon cancer has not been widely investigated. Aim of this study is to identify differentially expressed genes (DEGs) associated with cancer pathways in peritumoral adipose tissue compared with adjacent normal adipose tissue in human colon cancer. Methods: Fresh peritumoral and distal adipose tissue samples were collected from 6 patients undergoing surgery for colon cancer stage T3/T4. DEGs were identified employing Nanostring PanCancer Pathway Panel including 770 cancer-associated genes. Criteria for differential expression included p-value <0.05, fold-change greater than 2-fold and average normalised expression greater than 3. Five upregulated DEGs with the highest logarithmic fold change and 2 down regulated genes were validated using quantitative real-time polymerase chain reaction (RT-PCR). Protein expression of significantly DEG was evaluated with immunohistochemistry (IHC) in tumour tissue, peritumour adipose tissue and distal adipose tissue slides. Results: A total of 64/770 DEGs were identified in peritumoral adipose tissue compared to distal adipose tissue. Up-regulated genes (28.1%) included COL1A1, SFRP2, FGF7, PLA2G2A, NGFR and SFRP2. Down regulated genes (71.9%) included LEF1 and CDH1. Differential expression was validated with qRT-PCR (COL1A1 p=0.007; SFRP2 p=0.057; FGF7 ns; PLA2G2A ns; NGFR ns; LeF1 p=0.03; CDH1 p=0.09). IHC revealed differential distribution of COL1A1 showing maximum expression in tumor tissue decreasing at more distant sites. Conclusion: Our results have shown altered cancer associated pathways in peritumour stromal compartment, including down-regulation of Wingless/Integrated (WNT) pathway. Furthermore, we have identified significant up regulation of COL1A1 in peritumour adipose tissue compared to distal adipose tissue. COL1A1 may have a role in local invasion and distant metastasis, possibly mediated by SFRP2, a known pro-collagen c proteinase enhancer and WNT antagonist. SFRP2 and COL1A1 may represent potential stromal therapeutic targets in colon cancer.